Comparative Nephroprotective Effects of Extracts of Buchholzia coriacea on some Biochemical Parameters in Carbon Tetrachloride-induced Toxicity in Rattus novergicus (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Buchholzia coriacea (wonderful kola) is a medicinal plant that has been used worldwide as an alternative medication to promote human health. Comparative nephroprotective effects of crude seed powder, aqueous and methanolic extracts of B. coriacea in hepatotoxic rats was investigated for 56 days. The crude powder (BCCP), aqueous extract (BCAE) and methanolic extract (BCME) significantly reduced (p